Ethnobotanical study of wild edible fruits in eastern Bhutan - Pema Yangdon; Tetsuya Araki; Yen Yen Sally Rahayu; Kunzang Norbu (BMC, 2022)
Abstract Background In the past, wild edible fruits (WEFs) were a significant source of food and nutrition in Bhutan. These nutrient-rich species can enhance food security and alleviate poverty in Bhutan. However, recent developments like the introduction of improved fruit varieties, changes in dietary choices, and infrastructure development are expected to influence indigenous knowledge and consumption of WEFs. We aimed to document the species diversity of WEFs and their uses in eastern Bhutan and examine how the knowledge and consumption of WEFs vary with socio-demographic factors. Methods A total of 97 households in two districts were selected to participate in the survey. A semi-structured questionnaire was used to interview a selected adult from each household. Comparative analysis of indigenous knowledge and consumption of WEFs among the socio-demographic factors was performed using one-way ANOVA and a Chi-square test on R software. Results The present study reported 52 species of WEFs belonging to 35 families. The prevalence of WEF consumption was found to be 42%. WEF consumption differed significantly between districts, age groups, and indigenous knowledge levels. Similarly, indigenous knowledge of WEFs was significantly associated with districts and age groups. Conclusions Eastern Bhutan has a rich diversity of WEFs, but their consumption has been decreasing. Recent agricultural and infrastructure developments may have impacted the consumption and indigenous knowledge of WEFs in this region. Thus, domestication and agro-processing of WEFs should become a major focus in Bhutan to utilize their nutritional value and potential economic benefits to enhance food security in the country. Additionally, incorporating WEF-related knowledge in the school curriculum is essential to educate younger generations on WEFs.